Trade policy and economic welfare - Corden, W. M. (Warner Max); Oxford University Press (Oxford : Clarendon, 1974)
Expounding the normative theory of trade policy, this text sets out a framework for analysing trade and other intervention policies in the presence of domestic distortions.
Includes bibliographical references and index.
Keywords: Commercial policy; Protectionism